Photophysics of crystal violet lactone in reverse micelles and its dual behaviour1. Issue 68 (25th July 2015) - Maity, Banibrata; Chatterjee, Aninda; Ahmed, Sayeed Ashique; Seth, Debabrata
<x xml:space="preserve">Abstract</x> The photophysics of Crystal Violet Lactone (CVL) in aqueous and non aqueous reverse micelles (RMs) have been studied. It was observed that in RMs, the CTA → CTB transformation is retarded.